PERANCANGAN SISTEM E-LEARNING KURSUS ONLINE BERBASIS WEB MENGGUNAKAN LARAVEL - Naufal Yudhi Handika; Wirda Fitriani; Suherman (CV. Hawari, 2025)
The advancement of information technology has significantly impacted the field of education, particularly in the implementation of online learning (e-learning). This study aims to design and develop a web-based e-learning system for online courses using the Laravel framework. The system is designed to facilitate interactive learning between instructors and course participants, featuring user management (admin, teacher, student), course management, learning materials, payment transactions, and student progress tracking. The system development methodology follows the SDLC (System Development Life Cycle) approach, which includes requirements analysis, system design, implementation, and testing stages. Laravel was chosen as the framework because it supports structured, secure, and efficient web application development. The result of this research is a responsive and user-friendly e-learning system that effectively supports distance learning. This system is expected to serve as an alternative solution for providing an online course learning platform that is flexible and accessible anytime and anywhere.